Early Morbidity and Mortality Following In Utero Exposure to Selective Serotonin Reuptake Inhibitors: A Population-Based Study in Western Australia - Colvin, Lyn (Springer International Publishing, 2012)
BACKGROUND: The early years of life have a profound effect on a child’s developmental pathway. The children born to mothers suffering from depression may be at risk of increased morbidity and mortality in the first years of life. OBJECTIVE: The objective of this study was to investigate the hospital admissions and mortality of children whose mothers were dispensed a selective serotonin reuptake inhibitor (SSRI) during their pregnancy. METHODS: This was a population-based study of all pregnancy events in Western Australia (WA) from 2002 to 2005. The study used linkable state health administrative data from the WA Data Linkage System (WADLS) and the national Pharmaceutical Benefits Scheme (PBS), enabling birth outcomes, hospital admissions and deaths to be ascertained for the children of women dispensed an SSRI during their pregnancy. RESULTS: There were 3764 children born to 3703 women who had been dispensed an SSRI during their pregnancy (3.8% of all pregnancies in WA, 2002–5), and 94 561 children born to 92 995 women who had not been dispensed an SSRI. Mean birth weight, length and APGAR score at 5 minutes were significantly lower in children of women dispensed an SSRI, regardless of whether the SSRI was dispensed in trimester 1, or, trimester 2 or 3 only. 0.9% of the live born children in the SSRI group had died before the age of 1 year compared with 0.5% of the non-SSRI group (odds ratio [OR] 1.8; 95% CI 1.3, 2.6). Before the age of 2 years, 42.9% of the children in the SSRI group had been admitted to hospital after their birth admission, compared with 34.1% of the non-SSRI group (OR 1.4; 95% CI 1.3, 1.6). The most common reason for admission to hospital was acute bronchiolitis (OR 1.6; 95% CI 1.3, 1.8), with an increased risk seen in children of mothers who did not smoke during their pregnancy (OR 1.7; 95% CI 1.4, 2.0). CONCLUSIONS: The children in the SSRI group were more likely to be admitted to hospital in the first years of life, and this may reflect their prenatal exposure to SSRIs, be related to maternal depression, or SSRI use may be a proxy for an environmental exposure such as smoking, or a combination of these factors. Although the numbers of deaths in the first year of life were small, the increased risk of death in the first year of life in the SSRI group (OR 1.8; 95% CI 1.3, 2.6) is a new finding and should be investigated further.